Muallaf - Muhammad Adnan Irfiyanto (SELONDING, 2017)
Muallaf composition is a representation of a process of transfer of beliefs from a Muchlis biography. Muallaf means the person who has established himself to embrace the teachings of Islam, it is experienced by Muchlis who previously had the confidence of Confucius, until influenced by the habits of Muslims until in the end he pledged to Islamic teachings. The presentation of Muallaf composition is a mixture of ethnic, western and vocal instruments. It also adopted some patterns or motifs of the beats from several traditions such as Banyuwangi, Karawitan Java, and Betawi which later developed with techniques to work on music. The existing form of presentation based on phenomena that have been studied based on history or travel Muchlis, in general there are two parts in this work is the atmosphere when there is in Confucian Confidence, until the transition to embrace Islam. The music presented in this composition tends to see and take on an atmosphere that follows the plot of the Muchlis journey, in the Confucian section of the atmosphere that will present Chinese music, and then split again into sections to form variations, dynamics and musical expressions which is different, will then enter the Islamic section as the door of Muchlis embraced Islam, the music presented will be more inclined to the musical music of Islamic nuances with media such as bedug, gambus, tambourine and flute that plays melodis with Minor Zigana scales.Keywords: Muallaf, Transitional, Kong Hu Cu, Islam.